Morphological Identification and Prevalence of Gastrointestinal Helminths in Backyard Chicken From Selected Areas of Bangladesh - Abdullah, SM; Barman, Amrito; Ali, Md Yakub; Islam, Md Saiful; Mohanta, Uday Kumar (Research in Agriculture Livestock and Fisheries, 2021)
Poultry industry is the promising sub-sector in livestock, which has been expanding day by day. Among the poultry species, backyard chicken is one of the appropriate incomes generating species in rural areas of Bangladesh. Parasitic infections have been considered as one of the major hindrances for backyard chicken rearing. Therefore, the present study aimed to investigate the prevalence of gastrointestinal helminths of backyard chicken in some selected areas of Bangladesh through their detailed morphological identification. A total number of 108 gastrointestinal tracts were examined for helminths from April 2018 to July 2018. The collected helminths were identified according to the keys and description of Yamaguti (1961) and Soulsby (1982). A high rate of helminth infection (100%) was observed in backyard chickens in Bangladesh. One cestode, Raillietina tetragona (67.59%); two nematodes, Ascaridia galli (43.51%) and Heterakis gallinarum (28.70%); and two trematodes, Catatropis verrucosa (21.29%) and Echinostoma revolutum (6.48%) were encountered during the study. Most of the helminths were recovered from small intestine followed by caecum. All five species of helminths were found from Dhaka and Pabna, but surprisingly no trematodes were found from Bandarban. Out of 108 chickens, 29.62% were infected with single species of helminths while the rest 70.38% harbored mixed infections. This work strongly suggests that helminths create serious problems in backyard chicken as they hamper production and therefore, appropriate control strategies are needed to design for better production. Res. Agric., Livest. Fish.8(1): 145-155, April 2021